Modelling the risks of "smart city" development as a complex sociotechnical system - Kruglikov, S. V.; Davydovskii, A. G. (Informatika (Minsk, Belarus), 2025)
Objectives. The exponential growth of urbanized territories and urban populations required the development of new models and methods for describing and optimally managing the risks of modern cities as large and complex social, technological, and logistical systems. The paper is devoted to the problem of analyzing the risks of the development of a "smart city" as a complex sociotechnical system from the standpoint of the hypothesis of seven generations of "smart cities" using elements of mathematical modeling. Methods. The analysis of literary sources, modeling the seven generations of the "smart city" as a complex sociotechnical system based on linear differential equations and a numerical analysis of the development of the "smart city" concept are used. Results. The general characteristics of the "smart city" concept are presented and the risks of disruption of services and processes of the "smart city" are considered. The hypothesis of seven generations of the "smart city" is substantiated. Systems of linear differential equations have been developed that characterize each of the generations of the "smart city". An approach to modeling and assessing the integrated risk of a "smart city" is proposed. Conclusion . Systems of linear differential equations have been developed that characterize each of the seven generations of the "smart city", as well as the risks associated with them. A generalized model of integrated risk assessment of a "smart city" as a complex sociotechnical system based on a nonlinear differential equation is proposed. The fundamentals of the methodology for managing the risks of disorganization of services and life processes for different generations of the "smart city" as an evolving sociotechnical system are formulated